Implementation of Blockchain Technology to Enhance Transparency and Sharia Compliance in Islamic Financial Institutions in Indonesia - afif badawi (Universitas Muhammadiyah Sumatera Utara, 2026)
Islamic financial institutions in Indonesia continue to face structural challenges in ensuring transparency and consistent Sharia compliance due to the limitations of centralized information systems, which are prone to manipulation, limited auditability, and weak verification mechanisms. In the context of Indonesia’s rapidly expanding Islamic finance sector—valued at over USD 130 billion—and supported by the world’s largest Muslim population, the adoption of advanced digital technologies has become increasingly urgent. This study investigates the implementation of blockchain technology as a transformative instrument to enhance transparency, strengthen Sharia compliance, and modernize operational governance within Indonesian Islamic financial institutions. Employing a mixed-methods research design, the study integrates qualitative case studies of three major Islamic banks with quantitative analysis of blockchain implementation outcomes. Data were obtained through semi-structured interviews with 45 key stakeholders, including Sharia scholars, bank executives, IT professionals, and regulators, supported by technical evaluations of blockchain pilot programs and comparative system analysis. The findings demonstrate that blockchain adoption significantly improves real-time auditability, accelerates Sharia compliance verification processes, and enhances stakeholder trust through immutable transaction records and automated smart-contract mechanisms. Permissioned blockchain architectures are identified as the most suitable model for Islamic banking contexts, balancing transparency, data privacy, and regulatory requirements. This research offers a comprehensive framework for blockchain integration in Islamic finance and provides strategic insights for policymakers and practitioners seeking sustainable digital transformation.